PENGARUH EKONOMI MASYARAKAT PESISIR MELALUI DEVERSIFIKASI PRODUK KERUPUK UDANG DI DESA PUNTI SOROMANDI: Economic Influence Of Coastal Communities Through Shrimp Cracker Product Deversification In Punti Soromandi Village - Putri, Nurul; Maulana, Agus; Raodah, Raodah; Iklimah, Nur; Yusari, Yusnia; Annisah, Annisah; Mahyudin, Mahyudin; Fadhillah, Adyatma; Hayril, Hayril; Wahyuramadhan, Wahyuramadhan; Amirulmukminin, Amirulmukminin; Kusumayadi, Firmansyah (Al-Amal: Jurnal Pengabdian Masyarakat, 2025)
This study aims to improve the coastal community's economy through the diversification of shrimp cracker products in Punti Village, Soromandi District, Bima Regency. The method used is a participatory approach involving training, assistance, and product innovation. The results of the activities show that product diversification—such as spicy shrimp crackers, mini shrimp crackers, and premium-packaged shrimp crackers—can increase both market value and market reach. The community has begun to demonstrate independence in production and marketing. Through a collaborative and innovative approach, product diversification has proven effective as a strategy for strengthening the local economy